2021
DOI: 10.3389/fphar.2021.771046
|View full text |Cite
|
Sign up to set email alerts
|

Biejiajian Pill Promotes the Infiltration of CD8+ T Cells in Hepatocellular Carcinoma by Regulating the Expression of CCL5

Abstract: Tumor-infiltrating CD8+T lymphocytes are mostly associated with a favorable prognosis in numerous cancers, including hepatocellular carcinoma (HCC). Biejiajian Pill (BJJP) is a common type of traditional Chinese medicine that is widely used in the treatment of HCC in China. Previous studies showed that BJJP suppressed the growth of HCC cells both in vivo and in vitro, by exerting direct cytotoxic effects on tumor cells. The present study demonstrated that in addition to direct cytotoxicity, BJJP inhibits the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…While CD68+ macrophages are associated with poor prognosis, a significant decrease in CD68+ macrophage infiltration has been found in hepatocellular carcinoma peritumoral TLS ( 78 ). High expression of CCL5 significantly suppresses the development of tumor cells, but its ability to increase the ratio of M2/M1 macrophages promotes the progression of cancer ( 79 ). DCs promote lymphocyte infiltration and production of TLSs, inhibit tumor growth, and play an antigen-presenting role in TLSs.…”
Section: Pancreatic Cancer and Tlsmentioning
confidence: 99%
“…While CD68+ macrophages are associated with poor prognosis, a significant decrease in CD68+ macrophage infiltration has been found in hepatocellular carcinoma peritumoral TLS ( 78 ). High expression of CCL5 significantly suppresses the development of tumor cells, but its ability to increase the ratio of M2/M1 macrophages promotes the progression of cancer ( 79 ). DCs promote lymphocyte infiltration and production of TLSs, inhibit tumor growth, and play an antigen-presenting role in TLSs.…”
Section: Pancreatic Cancer and Tlsmentioning
confidence: 99%
“…Studies have shown that CCL-5 can activate and recruit M2 macrophages in HCC, increase the proportion of M2/M1 macrophages, and promote HCC progression ( 126 , 127 ). However, in a study on Biejiajian Pill and yttrium-90 (Y90) radioactive embolism (RE), CCL-5 expression was found to significantly suppress tumor cells ( 128 , 129 ).…”
Section: The Value Of Tls For Phc Treatmentmentioning
confidence: 99%